Effects of combined strength and power training on physical performance and interlimb asymmetries in adolescent female soccer players - Pardos-Mainer, E.; Casajús, J. A.; Bishop, C.; Gonzalo-Skok, O. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine the effects of an 8-week combined strength and power training intervention on physical performance and interlimb asymmetries in adolescent female soccer players. Methods: Thirty-seven adolescent female soccer players (age 16.1 [1.1] y) were randomly assigned to a control group (n?=?18) or experimental group (n?=?19). The experimental group performed combined strength and power training twice a week, which consisted of strength and power exercises that trained the major muscles of the lower body and trunk musculature. Preintervention and postintervention tests included unilateral and bilateral horizontal and countermovement jump tests, a 40-m sprint test (10- and 30-m split times), a 10-m sprint with a 180° change-of-direction (COD) test, and a multiple-COD test (V-cut test). Asymmetries were also analyzed in the unilateral tests. Results: Significant group-by-time interaction of the improvement between pretest and posttest was observed for speed (effect size [ES]: -1.30 to -1.16) and COD tests (ES: -0.62 to -0.61) but not in jumping (ES: -0.09 to 0.28) and interlimb-asymmetry tests (ES: -0.13 to 0.57). Conclusions: The short-term in-season combined strength and power training program induced greater speed and COD performance improvements than soccer training alone in adolescent female soccer players.Auswirkungen des kombinierten Kraft- und Schnellkrafttrainings auf die körperliche Leistungsfähigkeit und die Asymmetrien zwischen den Extremitäten bei Nachwuchsfußballspielerinnen